The Impact of the Environment and People’s Attitudes on Greywater Management in Slum Coastal Settlements - Idawarni Asmal; Edward Syarif; Samsuddin Amin; Muhammad A. Walenna (Salehan Institute of Higher Education, 2022)
The rapid population growth in many countries will ultimately impact the provision of essential services and engender many challenges, such as inadequate sanitation. Indonesia has an extensive coastline and densely populated coastal areas that have grown sporadically, creating slums. These areas have long been associated with poor greywater management. Greywater is dumped into beaches, roads, and yards without pre-treatment, thus harming the environment and society. This study aims to identify various factors influencing community actions to manage and overcome greywater-related problems in coastal slum areas. Using methods by combining qualitative and quantitative approaches. The influential factors in the physical condition of the built environment, the natural environment, community activities, and government involvement related to greywater were analyzed qualitatively, while the public understanding of greywater management was assessed quantitatively. The results showed that these four factors significantly influenced people's attitudes towards wastewater treatment. The findings show that these four factors affect people's mind-set about handling greywater, which becomes an obstacle to changing their attitudes and views on greywater. The four factors have the same level and cannot be separated in dealing with greywater. Treatment strategies are in accordance with coastal nature, settlements physical conditions and communities are then chosen Treatment Horizontal Flow. Doi: 10.28991/CEJ-2022-08-12-05 Full Text: PDF